Trends in Post‐Mastectomy Reconstruction in an Asian Population: A 12‐Year Institutional Review. Issue 1 (16th September 2016) - Ng, Yvonne Ying Ru; Tan, Veronique Kiak Mien; Goh, Terence Lin Hon; Yong, Wei Sean; Wong, Chow Yin; Ho, Gay Hui; Madhukumar, Preetha; Ong, Kong Wee; Ong, Yee Siang; Sim, Yirong; Tan, Bien Keem; Tan, Benita Kiat Tee
Abstract: Post‐mastectomy breast reconstruction is an integral component of breast cancer treatment. It is often perceived that women in Asian countries have a lower rate of post‐mastectomy reconstruction than Western populations. This study describes trends in timing and types of breast reconstruction performed in the largest healthcare provider in Singapore, over a period of 12 years. It also reports on the oncological outcomes and surgical safety. A retrospective review of all patients who underwent post‐mastectomy reconstruction from January 2001 to December 2012 at the National Cancer Centre Singapore and Singapore General Hospital was performed. Six hundred and twenty post‐mastectomy reconstructions were performed in 579 patients. The proportion of reconstructions increased from 4% in 2001 to 18% in 2012. Younger patients (<50 years old) and those with early stage cancer were more likely to undergo reconstruction. Immediate breast reconstruction was favored by more than 90% of patients. Postoperatively, 9% developed acute surgical complications that were treated surgically; 6% had additional surgery for late complications. Only 4% had delay of adjuvant chemotherapy. At median follow‐up of 63 months (range 3–166), loco‐regional recurrence was 4%, and distant metastases 8%. Post‐mastectomy reconstruction for breast cancer is increasingly performed in our institution. Both younger age and lower stage disease were associated with choice for reconstruction in our study. Low rates of delay to adjuvant therapy were noted, and it may safely be offered to suitable women undergoing mastectomy.